A Unique Theatre Miracle: Thirty-five Years of the Romani Pralipe Theatre (1971-2006): Своевидно театарско чудо: Триесет и пет години Театар на Ромите „Пралипе“ (1971-2006) - Lužina, Jelena; Koshka Hot, Rajna (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Jelena Lužina | Јелена Лужина Title (English): A Unique Theatre Miracle: Thirty-five Years of the Romani Pralipe Theatre (1971-2006) Title (Macedonian): Своевидно театарско чудо: Триесет и пет години Театар на Ромите „Пралипе“ (1971-2006) Translated by (Macedonian to English): Rajna Koshka Hot | Рајна Кошка-Хот Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 279-299 Page Count: 20 Citation (English): Jelena Lužina, “A Unique Theatre Miracle: Thirty-five Years of the Romani Pralipe Theatre (1971-2006),” translated from the Macedonian by Rajna Koshka-Hot, Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 279-299. Citation (Macedonian): Јелена Лужина, „Своевидно театарско чудо: Триесет и пет години Театар на Ромите ,Пралипе‘ (1971-2006)“, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 279-299.